PENGARUH LATIHAN FOOTWORK TWO STEP TERHADAP KELINCAHAN ATLET TENIS MEJA PUTRA SMA NEGERI OLAHRAGA PROVINSI RIAU - Elva, Maryan; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations conducted by researchers on male table tennis athletes at the Riau Province Sports High School, researchers found a problem that was a lack of agility in playing table tennis, such as athletes unable to move freely, in returning balls that came and could not be returned properly. The purpose of this study was to determine the effect of footwork two-steps exercise on the agility of a male table tennis athletes at the Riau Province Sports High School. The population in this study were table tennis athletes in the men's group that consist of 6 peoples. Sampling is determined by taking the all of population into samples (total sampling). This study used an experimental method, in order to determine the effect of footwork two-steps exercise. This experiment consist of pre-test, treatment with footwork two-steps exercise and post-test. The instrument of this study used a shutle run test. The analysis technique uses the t-test. Based on the t-test analysis produces Tcount of 2.681 and ttable 2.015. Means that Tcount > Ttable. It can be concluded that Ho is rejected, at the level of alpha (α) 0.05. so it can be summed “there is an effect of footwork two steps on the agility of the male table tennis athletes at Riau Province Sports High School. Based on the results obtained it is known that using footwork two-step exercise can improve agility, although statistically it shows a relatively small effect. So that in this study it can be concluded as follows: there is an effect of footwork two-steps exercise on the agility of the male table tennis athletes at Riau Province Sports High School.Key Words: Footwork Two Step Training, Agility